Exercise, Energy Balance, and Cancer - Ulrich, Cornelia M.; Steindorf, Karen.; Berger, Nathan A. (Energy Balance and Cancer ;, 2013)
Although it is well established that the worldwide pandemic of overweight and obesity has profound effects on promoting cancer, it is now recognized that alternative aspects of energy balance, namely physical activity and exercise have significant beneficial effects on all aspects of cancer across the spectrum from prevention through treatment and extending through survivorship. While the effect of physical activity and exercise on cancer may be partially mediated through obesity control, it is clear that considerable research is required and is ongoing at both the molecular and clinical levels to better understand the associated mechanisms and to develop optimal exercise strategies. This volume presents the effects of exercise on biological pathways in tumor growth, state of the art exercise strategies and cutting edge research focused on different cancers and patient groups. This important text will provide a basis for ongoing research, experimental approaches and application of evidence based practices to clinical care for patients with cancer.